Comparative analysis of the situational efficiency parameters of basketball players in two regional ABA leagues - Colakhodzic, E.; Sesar, T.; Popo, A. (Homosporticus, 2020)
The parameters of situational efficiency in basketball are interrelated and represent the interaction of technical, tactical, fitness and all other factors relevant to success. By registering and analyzing the parameters of basketball players' situational efficiency, it is possible to arrive at precise values of playing and team efficiency, which provide guidelines for more successful planning and programming of training technology. The aim of the study is to identify differences in situational efficiency parameters between the first and second regional ABA Basketball Basis, based on statistics made up of the individual performance of each basketball player within the team. The study was conducted on a sample of 24 clubs from two ABA leagues, in the regular competition for the 2018/19 season. Variables make the frequencies of successfully and unsuccessfully executed elements of technical and tactical action during the match in the stages of attack and defense. The data was downloaded from the official website swww.aba-liga.com and www.druga.aba-liga.com. Nine variables were taken to assess situational efficiency: 1. Average of balls inserted by 2 points (SHUT2P%); 2. Average of balls scored by 3 points (shot 3 P%); 3. Average free throws completed (FT%); 4. Defense Leap (SDEF); 5. Attack Jump (SOFF); 6. Assists (ASS); 7. Obtained balls (STE); 8. Lost Balls (TOURN); 9. Personal fouls (FOUL). Descriptive statistics were used for statistical data processing in order to better describe and understand the data set. The T-test for independent samples established statistical significance in the difference of situational efficiency parameters between the two regional leagues. There is a significant difference in the parameters of situational efficiency between the clubs performing in ABA1 and ABA2 regional league with two parameters, the average of balls inserted by 2 points (sig., 011) at the level of 95% significance, where the clubs from ABA2 regional had a better percentage. Basketball leagues and average personal fouls (sig..000), where, on average, more offenses were made in the ABA1 regional basketball league. Basketball players in two-regional ABA leagues differ statistically and significantly in 2 parameters of situational efficiency, shot by 2 points and personal mistakes. With all other parameters results exceeded the significance value of 95% (p <0.050).